La formación discursiva trascendentalista en la poesía costarricense contemporánea - Rodríguez Cascante, Francisco (2007)
In this article I propose the existence of a transcendentalist discursive formation in the diachronic trajectory in the Costa Rican poetry. The goal is to study the presence of this type of discourse in contemporary poetry, in particular that produced after 1980, without ignoring the evidence of this poetry in the lyric preceding that decade. Such a discursive formation is taken to include lyric groups in which: a) at the enunciative level one can see the presence of monodic enunciations with a figurative and abstract nature, b) the representational level consists of groups in which one can construct autonomous areas of an auratic-essentialist condition. I also argue that the meta-physical sustantialism assumed in this discursive formation has consolidated in the national cultural literary field thanks to the classification models historically legitimated in the Occidental literary works; these have contributed to maintaining it via an institutional fetishization process in the artistic production, in its association with the auratic- substantial dimension of aesthetics.